Women's Empowerment Through The Women Farmers Group Program In Patangkai Village Bone Regency - Marlina Rajab (Pt. Anagata Sembagi Education, 2024)
This study aimed to assess the empowerment of women, employing a qualitative research approach with a descriptive research type. The research focused on key figures such as the Head of Patangkai Village, Chairperson, Treasurer, and Secretary of the Women Farmers Group (KWT), as well as the community members. Data collection involved various techniques, including observation, interviews, and documentation, ensuring a comprehensive understanding of the empowerment process. To enhance the data's validity, source triangulation and technical triangulation were implemented. The analysis followed a systematic approach, encompassing data collection, reduction, presentation, and drawing conclusions. The findings revealed that the empowerment process through the KWT program exhibited positive outcomes in terms of planning and implementation indicators. However, the evaluation indicators demonstrated a shortfall, indicating a suboptimal level of goal achievement in the women's empowerment process. This study sheds light on the nuanced dynamics of women's empowerment within the KWT program. While planning and implementation aspects showcase success, the evaluation phase indicates a need for further scrutiny and improvement. Recognizing these intricacies is vital for refining and optimizing women's empowerment initiatives, ensuring their effectiveness and impact align with the intended goals. Moving forward, future efforts should focus on addressing the identified gaps in the evaluation process to enhance the overall success of women's empowerment through the KWT program.